Atomic Force Microscopy in Molecular and Cell Biology (Springer Singapore, 2018)
The book addresses new achievements in AFM instruments - e.g. higher speed and higher resolution - and how AFM is being combined with other new methods like NSOM, STED, STORM, PALM, and Raman. This book explores the latest advances in atomic force microscopy and related techniques in molecular and cell biology. Atomic force microscopy (AFM) can be used to detect the superstructures of the cell membrane, cell morphology, cell skeletons and their mechanical properties. Opening up new fields of in-situ dynamic study for living cells, enzymatic reactions, fibril growth and biomedical research, these combined techniques will yield valuable new insights into molecule and cell biology. This book offers a valuable resource for students and researchers in the fields of biochemistry, cell research and chemistry etc.